Large scale uniform Ni-P plated carbon fiber for boosting urea electro-oxidation and electro-detection - Fan, Yan-Ru; Li, Jin-Qi; Yang, Yu-Xi; Zhang, Zhi-Hao; Zhang, Jie; Yang, Jing-He (Frontiers in Chemistry, 2023)
Phosphorus doped nickel plating on carbon fibers (Ni-P/CF) is synthesized by simple electroless plating. SEM results exhibit that the Ni-P densely and uniformly grows onto the surface of carbon fibers (CF), forming carbon fibers-like nanoarchitectures. Benefiting from the carbon fibers-like nanoarchitectures with abundant exposed active sites on the surface of CF, electron transfer can be synchronously facilitated, and Ni-P/CF displays superior urea electrooxidation (UOR) performance with potentials of 1.40 V to reach 100 mA cm -2 . Impressively, it can maintain at 20 mA cm -2 for 48 h without evident activity attenuation, demonstrating robust durability. Cycle stability shows that the voltage has only increased by 10 mV at 300 mA cm -2 from 10th to 20000th cycles. Most importantly, Ni-P/CF at a length of 100 cm with good reproducibility was successfully synthesized, denoting great 2 potential for large-scale industrial production. Therefore, this work not only affords cost-effective tactics for urea-rich wastewater degradation but also can achieve practical medical application.